Beyond Social Norms: Exploring the Drivers of Youth's Political Participation Via Social Media - Marta Santos; Mijail Naranjo-Zolotov; Le Anh Nguyen Long; Albert Acedo; Afshin Ashofteh; Manuela Aparício (Emerging Science Journal)
This study examines the factors driving online political participation among young adults by integrating the Theory of Reasoned Action and the Civic Voluntarism Model. Structural equation modelling was applied using survey data from 236 young adults to analyse the relationships between attitudes, subjective norms, psychological engagement, political interactions, and resource availability. The findings indicate that attitudes and psychological engagement—comprising political interest, efficacy, and involvement—are the primary drivers of online political participation. In contrast, subjective norms and resource availability have no significant effect, suggesting that online engagement is primarily self-motivated rather than influenced by social expectations or material constraints. Furthermore, political interactions shape subjective norms, but these norms do not significantly impact participation intentions. This study contributes to understanding youth political engagement in digital environments by demonstrating that intrinsic psychological factors outweigh external influences. The findings have practical implications for strategies aimed at increasing youth political participation through social media, emphasising the need to foster political interest and efficacy rather than relying on peer influence or resource provision. By refining existing models of political engagement, this research provides a clearer framework for understanding and enhancing youth participation in democratic processes through digital platforms.